OPTIMIZING PLASTIC WASTE MANAGEMENT THROUGH DECOMPOSITION EDUCATION AND ECOBRICK IMPLEMENTATION IN KEDUNGBOKOR VILLAGE - Ferry Ferdianto; Nurochman Andika; Muhammad Dzaky Noer Raehan; Bakhtiar Rifai; Lovania Haristiana (Ann Publisher, 2026)
Background. Waste problems remain an environmental challenge in rural communities, including Kedungbokor Village, Larangan District, Brebes Regency. Low public awareness of waste sorting and limited educational media on waste decomposition times lead to suboptimal waste management. Aims. This community service activity aims to increase community knowledge and participation in inorganic waste management by providing educational media on waste decomposition and training in making ecobricks. Methods. The implementation method uses a participatory approach, which includes the stages of problem identification, socialization, environmental education, application of simple technology, mentoring, and evaluation of activities. Result. The results of the activity show the installation of educational media on the decomposition times of various types of waste as a permanent source of information in the village environment, and the community's implementation of ecobrick-making practices. Conclusion. This program also increases public understanding of the importance of waste sorting and reducing plastic waste through the 3R (Reduce, Reuse, Recycle) principle. Implementation. This activity made an initial contribution to raising community environmental awareness, although the program's sustainability required continuous support from the village government and active community participation.